1978
DOI: 10.1039/p19780001243
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the compositae. Part 38. Structure and absolute configuration of gallicin, a new germacranolide from Artemisia

Abstract: Gallicin, a new germacranolide, w a s isolated from Arternisia rnaritirna gallica Willd and assigned structure (3a) on chemical and spectroscopic evidence. Its absolute configuration w a s determined by the fact that it can be converted to the dihydrosantamarin (5) by a biogenetic cyclization process.ARTEMIN (1) was earlier isolated from Artemisia maritima and now from the same species two more sesquiterpene lactones have been separated. One has been identified by its physical constants and spectral data as 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The n-butanol-soluble fraction was fractionated by repeated CC and semi-preparative HPLC to provide four flavoalkaloids (Figure 2): two novel pure compounds (1 and 2) and a mixture of two isomers (3a and 3b). At the same time, 12 known compounds were obtained from the Chinese commercial white tea, including gallicin (4), 24 (+)-catechin (5), 25 (−)-epicatechin (6), 25 gallic acid (7), 26 kaempferol (8), 27 procyanidin B2 (9), 28 kaempferol-3− 7-O-β-D-dirhamnoside (10), 29 epigallocatechin-(4β-8)-epicatechin-3-O-gallate (11), 30 EGCG (12), 31 1,6-di-O-galloyl-β-Dglucose ( 13), 32 1-O-galloyl-4,6-(−)-hexahydroxydiphenoyl-β-Dglucose ( 14), 30 and 1,4,6-tri-O-galloyl-β-D-glucose (15). 30 Compounds 1, 2, 3a, and 3b showed a similar IR spectrum, which suggested the presence of hydroxyl groups (broad peak around 3397 cm −1 ), carbonyl groups (1695 cm −1 ), and aromatic rings (1620 and 1539 cm −1 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The n-butanol-soluble fraction was fractionated by repeated CC and semi-preparative HPLC to provide four flavoalkaloids (Figure 2): two novel pure compounds (1 and 2) and a mixture of two isomers (3a and 3b). At the same time, 12 known compounds were obtained from the Chinese commercial white tea, including gallicin (4), 24 (+)-catechin (5), 25 (−)-epicatechin (6), 25 gallic acid (7), 26 kaempferol (8), 27 procyanidin B2 (9), 28 kaempferol-3− 7-O-β-D-dirhamnoside (10), 29 epigallocatechin-(4β-8)-epicatechin-3-O-gallate (11), 30 EGCG (12), 31 1,6-di-O-galloyl-β-Dglucose ( 13), 32 1-O-galloyl-4,6-(−)-hexahydroxydiphenoyl-β-Dglucose ( 14), 30 and 1,4,6-tri-O-galloyl-β-D-glucose (15). 30 Compounds 1, 2, 3a, and 3b showed a similar IR spectrum, which suggested the presence of hydroxyl groups (broad peak around 3397 cm −1 ), carbonyl groups (1695 cm −1 ), and aromatic rings (1620 and 1539 cm −1 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Si gel column chromatography of the crude extract, followed by rechromatography of selected fractions exhibiting antimicrobial activity and/or containing compounds that could be interesting from a pharmacological as well as a phytochemical point of view (e.g., sesquiterpene lactones), afforded the four flavones, santin ( 1 ), centaureidin ( 2 ), apigenin ( 3 ), and its 7- O -β-glucoside ( 4 ) . In addition, nine sesquiterpene lactones, all belonging to a 12,6α-olide group (with 11αH configuration), have been isolated: 8α-hydroxy-1α,4α,5α,11βH-guaia-10(14)-en-12,6α-olide ( 5 , a new guaianolide), the elemanolide temisin ( 6 ), three germacranolides [balchanolide ( 7 ), 1β-hydroperoxy-8α-hydroxygermacra-4,10(14)-dien-6β,7α,11βH-12,6α-olide ( 8 ), shonachalin A ( 9 ) 13 ], and four eudesmanolides [11β,13-dihydroreynosin ( 10 ), 1β-hydroxy-6β,7α,11βH-selin-3-en-6,12-olide ( 11 ), 8α-hydroxy-11β,13-dihydrobalchanin ( 12 ), and artapshin ( 13 ) 15 ]. The lactones and flavones isolated previously from other plants were identified by comparison of their spectral data with the published ones.…”
mentioning
confidence: 99%
“…The chemical shifts and the values of the coupling constants of H-13 at δ H 1.14 (d, J=7.4 Hz) and H-11 at δ H 2.75 (dq, J=7.9, 7.8 Hz), as well as the chemical shift of C-13 at δ C 9.8, suggested that both H-7 and H-11 were in the cis-configuration relative to each other. 18,20,27) All these results established that 4 was 1β,3β,15-trihydroxy-germacra-4Z,10(14)-dien-6β,7α,11αH-12,6-olide and named zawadskinolide D.…”
Section: Resultsmentioning
confidence: 72%